Behavioral changes in FPR2/ALX and Chemr23 receptor knockout mice are exacerbated by prenatal alcohol exposure - Mooney, Sandra M.; Billings, Elanaria; McNew, Madison; Munson, Carolyn A.; Shaikh, Saame R.; Smith, Susan M. (Frontiers in Neuroscience, 2023)
Introduction Prenatal alcohol exposure (PAE) causes neuroinflammation that may contribute to the pathophysiology underlying Fetal Alcohol Spectrum Disorder. Supplementation with omega-3 polyunsaturated fatty acids (PUFAs) has shown success in mitigating effects of PAE in animal models, however, the underlying mechanisms are unknown. Some PUFA metabolites, specialized pro-resolving mediators (SPMs), play a role in the resolution phase of inflammation, and receptors for these are in the brain. Methods To test the hypothesis that the SPM receptors FPR2 and ChemR23 play a role in PAE-induced behavioral deficits, we exposed pregnant wild-type (WT) and knockout (KO) mice to alcohol in late gestation and behaviorally tested male and female offspring as adolescents and young adults. Results Maternal and fetal outcomes were not different among genotypes, however, growth and behavioral phenotypes in the offspring did differ and the effects of PAE were unique to each line. In the absence of PAE, ChemR23 KO animals showed decreased anxiety-like behavior on the elevated plus maze and FPR2 KO had poor grip strength and low activity compared to age-matched WT mice. WT mice showed improved performance on fear conditioning between adolescence and young adulthood, this was not seen in either KO. Discussion This PAE model has subtle effects on WT behavior with lower activity levels in young adults, decreased grip strength in males between test ages, and decreased response to the fear cue indicating an effect of alcohol exposure on learning. The PAE-mediated decreased response to the fear cue was also seen in ChemR23 KO but not FPR2 KO mice, and PAE worsened performance of adolescent FPR2 KO mice on grip strength and activity. Collectively, these findings provide mechanistic insight into how PUFAs could act to attenuate cognitive impairments caused by PAE.